South Africa : Tax Compliance Burden for Small Businesses : A Survey of Tax Practitioners - FIAS (World Bank, Washington, DC, 2021)
This report is focused on the survey of the compliance experience of professional accountants and bookkeepers in respect of their small business clients in South Africa. It will be complemented by two related surveys, one of small businesses that are registered with the South African Revenue Service (SARS), regarding their time and cost requirements for tax compliance, and one of informal businesses, regarding their perceptions about tax compliance. The purpose of the set of three surveys is to document estimated tax compliance costs for small businesses in South Africa, to identify the most onerous compliance burdens based on these costs in order to confirm and guide reform priorities, and to provide inputs towards the development of an educational campaign by SARS that will help to encourage tax compliance amongst small businesses in South Africa. It is envisaged that the surveys will also be used as a baseline against which future progress can be measured.